2018
DOI: 10.18203/2349-3291.ijcp20185204
|View full text |Cite
|
Sign up to set email alerts
|

Leave against medical advice from SNCU of a teaching hospital in Garhwal, Uttarakhand, India

Abstract: Background: Patients who leave against medical advice (LAMA) is a universal problem. Neonates being unable to decide for their own, are dependent on parents for all decisions for their treatment. LAMA is a sensitive issue in neonatology practice with ethical and medico legal ramifications. This study was done to evaluate the factors associated with the decision of LAMA by care givers in our special newborn care unit (SNCU).Methods: This is a retrospective hospital based observational study and was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 7 publications
4
16
2
Order By: Relevance
“…The prevalence of DAMA in this study was found to be very high at 25.7%. This finding is similar to the 22.24% and 25.4% reported from NICUs in India [ 12 , 13 ] but higher than Nepal (18%) [ 1 ] and Nigeria (11.2%) [ 3 ]. Emergency admission and admission to the neonatal intensive care unit itself was reported as a significant independent risk factor for DAMA [ 2 , 8 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The prevalence of DAMA in this study was found to be very high at 25.7%. This finding is similar to the 22.24% and 25.4% reported from NICUs in India [ 12 , 13 ] but higher than Nepal (18%) [ 1 ] and Nigeria (11.2%) [ 3 ]. Emergency admission and admission to the neonatal intensive care unit itself was reported as a significant independent risk factor for DAMA [ 2 , 8 ].…”
Section: Discussionsupporting
confidence: 88%
“…DAMA was more on festive and weekends than any other days of the week. Similar findings were found by Kumar et al and Turkistani et al [ 13 , 18 ] Discharge decisions were typically made by the mid level doctors with the consent of consultants on the morning following the round. Due to a lack of staff and hospital policy, the discharge rate with advice was lower in the evening and almost zero at night.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations